Si Ponyang at ang lihim ng kuweba - Atole, Melvin John B.; Geneblazo, Sarah M.; Suarez, Angelo V. (Quezon City : CANVAS, 2019)
Ponyang is a girl who quickly makes herself scarce after class, much to the curiosity of her good friend Potpot. (3z(BWhere could she be rushing to?(3y (Bwonders Potpot. One day, he follows her and arrives at a cave she has been frequenting. Here, new discoveries unfold.s
Winner of CANVAS Romeo Forbes children's storywriting competition
Keywords: Children's stories, Filipino